Environmental literacy-based on adiwiyata predicate at junior high school in Ponorogo - Siti Nurwaqidah; S. Suciati; Murni Ramli (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
The student's environmental literacy (EL) is vital to improving students' awareness of environmental issues. This study was intended to display the role of eco-school program (Adiwiyata) and non-adiwiyata schools towards EL of junior high school students by analyzing EL of students in Ponorogo. The research was conducted in March-October. The survey involved 379 students. The type of research is ex post facto. The assessment used the Middle School Environmental Literacy Survey (MSELS). The results show that the adiwiyata program is related to the increase of EL with the sig value. 0.000. The higher the adiwiyata level, the higher the EL value of the environment. However, the general EL assessment in Ponorogo is still low, that more than 51% of respondents did not reach the score at level 3, which is the standard level of EL. The EL ability of junior high school students between male and female sex is different, with the sig value. 0.004. All data analysis concluded that the level of students' EL was significantly influenced by school type and gender. EL of students may low due to students' lack of understanding of the environment concepts, the limited theories, and concepts transferred to students.